2012
DOI: 10.1016/j.tet.2012.04.077
|View full text |Cite
|
Sign up to set email alerts
|

Enantio-selective reduction of the flowering related compound KODA and its analogues in Pharbitis nil cv. Violet

Abstract: Plant oxylipins are an important class of signaling molecules in plants. The cyclic adducts of epinephrine or norepinephrine with the naturally occurring oxylipin (12Z,15Z)-9-hydroxy-10oxo-octadeca-12,15-dienoic acid (KODA, 1) or its synthetic analogues (2-6) have been reported to possess flower-inducing activity towards Lemna paucicostata. By in vivo and in vitro experiments with seedlings of Pharbitis nil cv. Violet carbonyl groups of the -ketols (1 and 3) and the ketones (7 and 9) were enantio-selectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…The recorded 1 H-and 13 C-NMR spectra are in very good agreement with those previously reported in the literature [42] for the same HFAs.…”
Section: Resultssupporting
confidence: 90%
“…The recorded 1 H-and 13 C-NMR spectra are in very good agreement with those previously reported in the literature [42] for the same HFAs.…”
Section: Resultssupporting
confidence: 90%
“…By comparison of the NMR, MS, and OR data with the references, 14 known compounds were identified as cyclo[Trp‐Gly] (3), [10] cyclo(Trp‐Ana) (4), [11] cyclo‐(Trp‐Ser) (5), [12] glioperazine C (6), [13] cyclo(Ala‐Tyr) (7), indazole (8), [14] 2‐(4‐hydroxyphenyl)‐2‐oxoethanol (9), [15] 2,2‐[bis‐4‐(2,3‐dihydroxypropoxy)phenyl]propane (10), [16] 2‐[4‐(2,3‐dihydroxypropoxy)phenyl]‐2‐[4′‐hydroxyphenyl]propane (11), furan‐2,5‐diyldimethanol (12), [17] 2,3‐butanediol (13), [18] ergosterol (14), [19] 10‐hydroxy‐cis‐12‐octadecenoic acid (15), [20] and oleic acid (16) [21] …”
Section: Resultsmentioning
confidence: 99%
“…On the basis of above evidence, 2 was then established as (2S,3S)-3-(1H-indol-3-yl)-3methoxypropane-1,2-diol, and named cladosporiole B. By comparison of the NMR, MS, and OR data with the references, 14 known compounds were identified as cyclo[Trp-Gly] (3), [10] cyclo(Trp-Ana) (4), [11] cyclo-(Trp-Ser) (5), [12] glioperazine C (6), [13] cyclo(Ala-Tyr) (7), indazole (8), [14] 2-(4-hydroxyphenyl)-2-oxoethanol (9), [15] 2,2-[bis-4-(2,3-dihydroxypropoxy)phenyl]propane (10), [16] 2-[4-(2,3dihydroxypropoxy)phenyl]-2-[4'-hydroxyphenyl]propane (11), furan-2,5-diyldimethanol (12), [17] 2,3-butanediol (13), [18] ergosterol ( 14), [19] 10-hydroxy-cis-12-octadecenoic acid (15), [20] and oleic acid (16). [21] All compounds were tested for antimicrobial activity against Vibrio parahaemolyticus.…”
Section: Resultsmentioning
confidence: 99%
“…However, many studies have shown that epinephrine and its analogue are crucial in the flowering. First, epinephrine can partly overcome the inhibition posed by sucrose-ammonium of flowering in [ 62 ] L.paucicostata [ 62 , 63 ]. Second, the antagonist of epinephrine and propranolol can inhibit the flowering of Lemna with an ammonium-free medium.…”
Section: Discussionmentioning
confidence: 99%